IKPM Sudan sebagai Community of Practice: Perspektif Teori Etienne Wenger tentang Pembelajaran Sepanjang Hayat di Kalangan Alumni Gontor - Muhammad Fadhil Hadziq; Muhammad Aqil Abror; Ahmad Mamduh; Risal Apriono; Muhammad Ismail Abdurrahman Shaleh; Muhammad In'am Khoodhi (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study aims to analyze how the Sudan Branch of the Modern Gontor Family Association (Ikatan Keluarga Pondok Modern [IKPM]) fosters lifelong learning through Etienne Wenger's Community of Practice perspective. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that IKPM Sudan embodies the four core characteristics of a Community of Practice. Mutual engagement is reflected in members' active participation in planning, implementing, and evaluating organizational programs, thereby promoting collaborative learning. Joint enterprise is demonstrated through a shared vision of alumni development by integrating academic, social, spiritual, and international networking activities. Shared repertoire is manifested in a sustained learning culture, literacy traditions, the publication of the Sintesa Bulletin, and systematic knowledge documentation passed on across generations. These practices collectively foster learning and identity, as evidenced by members' transformation into leaders, writers, moderators, and resource persons. This study implies that Islamic boarding school alumni organizations can be developed as non-formal educational ecosystems that support lifelong learning, strengthen alumni identity, and serve as a Community of Practice-based model for alumni development in Islamic educational institutions at both national and international levels.